Functional response of Trichogramma pretiosum on Trichoplusia ni eggs at different temperatures and egg densities - Milanez, André Malacarne; Carvalho, José Romário de; Lima, Victor Luiz Souza; Pratissoli, Dirceu (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to determine the functional response of the parasitoid Trichogramma pretiosum on Trichoplusia ni eggs at different temperatures (20, 25, and 30ºC) and egg densities (5, 10, 15, 20, 25, and 30 eggs). The logistic regression showed a type-II functional response for all temperatures. The search efficiency of T. pretiosum was reported as 0.049±0.0019, 0.069±0.0042 and 0.068±0.0033 per hour, and the estimated handling times were 1.82±0.0424, 1.69±0.0398, and 1.54±0.0498 hour at 20, 25 and 30ºC, respectively. Females of Trichogramma pretiosum show greater efficiency at 30ºC and a type-II functional response. The parasitism rate decreases, when host density increases.